INDEKS NILAI PENTING SERANGGA PADA PERKEBUNAN APEL SEMIORGANIK DAN ANORGANIK KOTA BATU - Nasirudin, Mohamad; Hidayat, Rohmat (Exact Papers in Compilation (EPiC), 2019)
This study aims to determine the Important Value Index (IVI) of insects that are present in plantations of semiorganic and anorganic apples in Tulungrejo Village, Bumiaji District, Batu City. Insect handling is done by direct observation and Yellow Trap. This research was carried out in April-May 2019. The parameters observed were insect IVI in both fields. The results of insect IVI research showed that the highest value in semiorganic apple plantations by direct observation found insects from the Cerambycidae family of 40.06% which acted as herbivores, while anorganic land from the Thripidae family was 42, 84% which acted as herbivor as well. Whereas the highest IVI in semiorganic and anorganic apple plantations with observations of Yellow Trap tools were found by insects from the family of Aphydidae namely semiorganic at 85.11%, and anorganic at 86.87% which acted as Herbivor.